Pengaruh Metode Drill Berdasarkan Ibrani 10:36 Terhadap Keaktifan Siswa di SD Negeri Cibojong - Femilina Nazara; Olis Olis (LPPM - STT Kadesi Bogor, 2024)
This study aims to evaluate the influence of Hebrew 10:36-based drill methods on student activity in Cibojong SDN. The results of the hypothesis test showed a significant influence, with a correlation value (R) of 0.950. The validity and reliability test stated that the data used was valid and reliable. The normality test showed normal distribution in the data population, while the linearity test rejected H0 and concluded the influence of the drill method on student activity. The data analysis concluded that there was a significant positive correlation between the Drill method and student activity of 94%. The findings of the study are supported by researchers' observations of students at Cibojong SDN, emphasizing the importance of physical, psychological, and environmental support in improving student activity. In this context, research concludes that the method of drill based on Hebrews 10:36 has a significant positive influence on student activity in Cibojong SDN. The practical implications of this study suggest the need for a learning approach involving drill methods to enhance student participation and understanding. The study also validated the initial hypothesis with a confidence rate of 94%, confirming that the drill method is effective in improving student activity in accordance with the theory and observational findings.